Identificación del nivel de estrés hídrico en las estribaciones del cerro Casahuala de la parroquia Pasa, provincia de Tungurahua. - Lasluisa Chacha, Andrés Sebastián (2023)
This thesis was developed in the Pasa parish of the Ambato canton of the Tungurahua province, the research was carried out to estimate the level of water stress in the foothills of Casahuala hill, whose study area is made up of 5089.88 hectares of communal lands. In which 2314, 53 ha, belong to paramo. This being a water catchment area from which 7631 inhabitants receive for agricultural, hydroelectric, fish farming, thermal, domestic, drinking, and tourist use.